Progress in the Research and Development of Anti-COVID-19 Drugs - Huang, Lianzhou; Chen, Yuanqiu; Xiao, Ji; Luo, Weisheng; Li, Feng; Wang, Yuan; Wang, Yiliang; Wang, Yifei (Frontiers in Public Health, 2020)
The outbreaks of COVID-19 due to SARS-CoV-2 has caused serious physical and psychological damage to global human health. The COVID-19 spread rapidly around the world in a short time. Confronted with such a highly infectious respiratory disease, the research and development of anti-COVID-19 drugs had become an urgent work due to the lack of specific drugs for the treatment of COVID-19. However, some treatment measures performed currently show an excellent activity of anti-COVID-19. In this review, we make a comprehensive summarization of current methods for the treatment of COVID-19. We also posed the strategies of the development of anti-COVID-19 drugs in the future. Our review would provide a novel insight into the future development of a safer, efficient, and toxic-less anti-COVID-19 drug.